Some older sources for Croatian exonym analysis - Crljenko, Ivana (Acta geographica Slovenica, 2014)
The article introduces the review of some older sources in the Croatian language that might be useful for the Croatian exonym analysis, and may also refer to the exonym status it the context of the Croatian language development and geographers' indifference concerning that issue. Because of frequent changes in orthography, geographical names (as well as exonyms) have experienced different modifications, which can be followed through eight analyzed editions published during the period from 1880 to 1974. It was indicated that geography as a profession has greatly failed in serious research of exonyms.